Does bank efficiency affect the bank lending channel in China? - Zuzana Fungáčová; Eeva Kerola; Laurent Weill (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
This work examines the impact of bank efficiency on the bank lending channel in China. Using a sample of 175 Chinese banks over the period 2006-2017, we investigate how the reaction of the loan supply to monetary policy actions depends on a bank's efficiency. While bank efficiency does not exert an impact on the effectiveness of monetary policy transmission overall, it does favor the transmission of monetary policy for banks with low loan-to-deposit ratios. In addition, the expansion of shadow banking activities has been associated with a positive impact of bank efficiency on monetary policy transmission. These results suggest that bank efficiency may influence the bank lending channel in certain cases.
URN:NBN:fi:bof-202002181135
Keywords: E52; G21; 330; Chinese banks; monetary policy; bank efficiency; bank lending channel